2016
DOI: 10.1136/ejhpharm-2016-001045
|View full text |Cite
|
Sign up to set email alerts
|

Does an interaction exist between ketamine hydrochloride and Becton Dickinson syringes?

Abstract: IntroductionAn international alert from Becton Dickinson (BD) has noted the possibility of interaction between several molecules and some syringes. The Centralized IntraVenous Additives Service of the institution was using 3 mL BD syringes to store ketamine HCl. This study evaluated the interaction between ketamine and these syringes.MethodA batch of BD syringes produced in Europe and left in quarantine from the day of the international alert has been tested at 22, 29, 36, 43 and 50 days of storage at room tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Stress degradation studies operating in different conditions from those used in this study have yielded four degradation products and one degradation product in alkaline condition for sufentanil and ketamine, respectively. Closset et al found no degradation products for ketamine . For these two drugs, our results revealed more degradation products, offering a wider opportunity to check for drug instability.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Stress degradation studies operating in different conditions from those used in this study have yielded four degradation products and one degradation product in alkaline condition for sufentanil and ketamine, respectively. Closset et al found no degradation products for ketamine . For these two drugs, our results revealed more degradation products, offering a wider opportunity to check for drug instability.…”
Section: Discussionsupporting
confidence: 51%
“…A previous study noted that a 1-mg/mL solution could be stored out of light and at ambient temperature for over 1 year. 13 Stress degradation studies operating in different conditions from those used in this study have yielded four degradation products 14 and one degradation product in 16 For these two drugs, our results revealed more degradation products, offering a wider opportunity to check for drug instability. This could be accounted for by the difference in elution conditions (eg, gradient elution mode and the geometry of our column) which contributed to improving analytical efficiency.…”
Section: Discussionmentioning
confidence: 64%
“…This is an indication that interaction between the package material and molecules of ketamine is unlikely, though interaction between ketamine and the packaging material might result in some degradation that may be hastened in higher temperature conditions. 2,3 Significant interaction between plastic syringes and molecules of drugs has been reported. 2 In tropical areas such as Africa, temperatures often exceed 30 °C, which is frequently experienced during mass casualty events and medical outreach activities.…”
Section: To the Editormentioning
confidence: 99%
“…2,3 Significant interaction between plastic syringes and molecules of drugs has been reported. 2 In tropical areas such as Africa, temperatures often exceed 30 °C, which is frequently experienced during mass casualty events and medical outreach activities. Drugs prepared in syringes may contain concentrations outside the designated range of acceptability.…”
Section: To the Editormentioning
confidence: 99%
“…Closset et al was able to show that ketamine is stable in a Becton Dickinson® (BD) syringe for up to 50 days. 10 Foy et al was able to determine that ketamine was stable at 33°C for at least 7 days in the patient-controlled analgesia systems between preparation and administration. 11 Huvelle et al reported that ketamine diluted in 3 mL propylene syringes may be chemically stable for up to 180 days at room temperature at 25°C, while Daouphars et al demonstrated that ketamine is stable in a polyvinyl chloride bag for 7 days at 23ºC, though ketamine was mixed with oxycodone in the latter.…”
Section: Ketamine Pharmacologymentioning
confidence: 99%